The Relationship between Audit Fees for City Specialists and Audit Quality in United Kingdom - HUANG, YANLING (2017)
This study examine the relationship between audit fees for city specialists and audit quality, which is measured by discretionary accruals and city specialists is proxied by market share and the largest market share in a specific industry and a specific city will defined as city expertise. And the interaction term SPEC*FEE is learnt from Lim and Tan (2010) as the measure of audit fees for city specialists. There are lots of hypotheses in my paper they include city specialists are positive associated with audit quality, audit fees are negative with audit quality, and because city specialists have higher audit fee premium, audit fees for city specialists should be not related to audit quality. Unfortunately, after running OLS regression for discretionary accruals, my study examine that audit fees are positive with audit quality, is consistent with Frankel et al. (2002) but not consistent with my hypothesis; also the results indicate that city specialists are not related to discretionary accruals which is same as the findings for MINUTTI‐MEZA (2013). Although they are out of my expectation, the association between audit fees for city specialists and audit quality is consistent with my hypothesis.